TEMPAT SINGGAH DUKUH ATAS STEPOVER PLACE - Marseno Sanjaya; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Based on data from PT Kereta Commuter Indonesia (KCI) the number of KRL passengers throughout 2017 reached 315.8 million passengers, up 12.55% from the previous year and will experience an increase every year. With this amount it is known that commuting has also increased. Areas that have easy access to public and strategic transportation are in the center of Jakarta's business district, Dukuh Atas. Hamlet above is also an area with a large commuter population. Every day commuters in Indonesia spend 2-third of their time just waiting and there is repetition. this causes things such as the individual's lack of attention to health, social world and also a high level of stress. Therefore, with the increasing number of passengers and the appropriate area a third place can be created which is a place between the first place and second place that drives humans to build community, equality, and also routines in terms of something positive. For that, we need a place to stop in order to increase productivity and also eliminate the saturation that arises due to repetition that occurs. Then a place was built that had programs such as a bed, a place to chat and also a green room. This building also had room for ticket information that was integrated directly with the Upper Hamlet Station which facilitated access and information accordingly such as departure hours and also when trains arrived.Abstrak Berdasarkan data PT Kereta Commuter Indonesia (KCI) jumlah penumpang KRL sepanjang 2017 mencapai 315,8 juta penumpang naik 12,55% dari sebelumnya dan akan mengalami peningkatan setiap tahunnya. Dengan jumlah ini maka diketahui bahwa komuter juga mengalami peningkatan. Daerah yang memiliki akses yang mudah untuk transportasi umum dan strategis berada di pusat bisnis Jakarta yaitu Dukuh Atas. Dukuh atas juga merupakan daerah dengan penduduk commuter yang besar. Setiap hari kaum komuter di Indonesia menghabiskan 2 per 3  dari waktunya hanya untuk menunggu dan ada pengulangan yang terjadi. hal ini menyebabkan hal seperti ketidakperhatian individu terhadap kesehatan, dunia sosial dan juga tingkat stress yang tinggi .Oleh karena itu, dengan adanya jumlah penumpang yang terus meningkat dan kawasan yang sesuai dapat diciptakannya third place yaitu suatu tempat di antara first place dan second place yang mendorong manusia untuk membangun komunitas,kesetaraan,dan juga rutinitas dalam hal yang bersifat positif.Untuk itu, diperlukan sebuah tempat untuk singgah agar dapat meningkatkan produktivitas dan juga menghilangkan rasa jenuh yang timbul akibat pengulangan yang terjadi. Maka itu dibangunlah sebuah tempat yang memiliki program seperti tempat tidur, tempat untuk bercengkrama dan juga ruang hijau.Bangunan ini juga mempunyai ruang untuk informasi tiket yang berintegrasi langsung dengan Stasiun Dukuh Atas yang mempermudah akses dan informasi yang sesuai seperti jam keberangkatan dan juga waktu kereta datang.